Efektivitas jelly buah bit terhadap kadar hemoglobin ibu hamil - Agustina, Winda; Harahap, Hasanah Pratiwi; Oktafirnanda, Yuka; Sembiring, Elya Rosa Br (Journal of Pharmaceutical and Sciences, 2023)
Introduction: During pregnancy, pregnant women must get lots of nutrients, such as calories, protein, iron, fat, which are useful for the growth of the fetus and for the health of the mother. Nutritional deficiencies can cause anemia, abortion, and other complications. In Indonesia, anemia is caused by iron deficiency, so it is better known as iron nutritional anemia. Iron deficiency anemia is one of the most common disorders during pregnancy. Iron is found in many food sources, including beets. Method: this type of quantitative research with pre-experimental design method with one group pretest- posttest design. The location of this research is in Helvetia Village, Sunggal District, Deli Serdang Regency. The sample in this study were pregnant women using the total population technique. The intervention was in the form of beet jelly. Measuring hemoglobin levels in pregnant women was carried out by checking Hb levels using the Easy Touch digital Hb examiner before and after the intervention. The data analysis used was an analysis of variance with a significance level of 95% (0.05). The result: this research are that the calculated average (mean) of the pretest and posttest for the beetroot jelly group is 1.1375 with a value of Sig. (2-tailed) is 0.007 where <0.05. Conclution: there is a difference between the calculated mean (mean) of the pretest and posttest for the beetroot jelly group, meaning that beetroot jelly is effective in increasing the hemoglobin levels of pregnant women.